PENGARUH DETERMINAN KONTEKSTUAL TERHADAP KEMATIAN IBU DI KABUPATEN KUPANG - Tirza Vivianri Isabela Tabelak; Yurissetiowati (STIKes Al-Insyirah Pekanbaru, 2022)
MDGs target that the maternal and newborn mortality rate is 102/100,000 births. Data obtained in 2015 showed that out of 100,000 live births in Indonesia, and 305 of them have maternal mortality. Maternal mortality in NTT Province was also contributed from Kupang Regency, in 2016 was 12 cases. The maternal mortality rate (reported) is 201.95 per 100,000 live births. The purpose of this study was to analyze the contextual determinants of maternal mortality in Kupang Regency. This research is a qualitative research. The research locations were 6 health centers with maternal deaths, namely Tarus, Sulamu, Takari, Poto, Camplong and Naikliu. The main informants subject were midwives coordinator in 6 Health Centers. The triangulation informants were the Head of the Community Health Center and stakeholder with a total of 6 people. The main instrument was that the researcher used an in-depth interview guide and a focus group discussion guide. The results of this study are contextual determinants that can affect maternal mortality, including knowledge, mother's education is still low on average (SD, SMP), housewife or seasonal farmers, mothers are powerless in terms of referral decision making, distance to health centers that are far, the absence of health workers in the village, pregnant women who do not have ANC, have chronic diseases or are at high risk, mothers give birth at home and are assisted by traditional birth attendants/family. The conclusion that can be drawn is that contextual determinants have a relationship with maternal mortality.